Face-to-Face versus Online or Hybrid: How Students Perceive the Educational Framework - Ioana Plescau; Catalin Drob (Ovidius University Annals: Economic Sciences Series, 2023)
In the aftermath of the recent pandemic, it became more and more important for the educational system to account for the necessity of designing courses that could be delivered both in an onsite environment and in an online framework. The aim of our study is to investigate perceptions of students about the face-to-face, online and hybrid learning. We conduct a survey to explore the way students perceive the educational frameworks. Our survey is conducted on a sample of students enrolled in the third and fourth year of study at the Faculty of Engineering from Vasile Alecsandri University of Bacau. From 126 respondents, 53% would choose hybrid framework. Moreover, 45% of them would choose to have the possibility of online courses and face-to-face seminars. Furthermore, 77% of the students work and they perceive blended/hybrid learning as a higher chance to participate to courses, without the necessity to physically attend the them.